GREEN WATER FRONT SEBAGAI UPAYA PENANGGULANGAN BANJIR DAN TATA LINGKUNGAN KUMUH DAERAH ALIRAN SUNGAI CILIWUNG - Muchlison, Muhammad Hadi; Naufal, Rizqullah Nazih; Syah, Mario Norman (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
River has strategic role as one of the natural resources that supports peoples lives. Ciliwung has the most widespread impact during the rainy season because it flows through the center of the city of Jakarta and across many villages, dense housing and slums. This paper aims to formulate a concept for managing a slum neighborhood on the banks or Ciliwung watershed. This concept is supported by the main concept of the Green Water Front. Based on the results of our analysis, it is known that the low citizens living in the area Ciliwung River in maintaining the environment. To increase awareness of citizens in maintaining the environment, we carry a concept of Green Water Front, which is the core of this concept will change as the river behind the house into the river as the front of the house. So the river will be a point of interest. On this concept there will be a bridge crossing over the river which we call the bridge